The Myth of Equal Opportunities: Why top grades of our students do not guarantee the best work? (Journal of Parents and Teachers, 2013)
A labor market with equal opportunities is characteristic of developed, intelligent, fair and caring societies. However, in our country, still we can find several examples of labor discrimination and occupational segregation because of gender reasons. Our school girls are effective users of mixed educational system. The fact that they obtain better preparation and worse employments suggest that an educational nonsense, a squandering of talent and a gender injustice. It is essential to work the Academic Professional Orientation educationally so that/in order that the students could design their futures in equality, without the traditional subordination of the feminine role to the masculine role as the key provider; and also without hinder the professional masculine development. In this article, there are different activities and resources to sustain the educational performance above mentioned from the conscience of the problems, of the strategic resources and of the need of exigency of a real co-responsibility that exist nowadays.
Keywords: Professional orientation; Equal opportunities; Employment of women; Discrimination; Money